Proteomics of endometrial cancer diagnosis, treatment, and prognosis. Issue 3 (15th December 2015) - Mittal, Parul; Klingler‐Hoffmann, Manuela; Arentz, Georgia; Zhang, Chao; Kaur, Gurjeet; Oehler, Martin K.; Hoffmann, Peter
Abstract : This review discusses the current status of proteomics technology in endometrial cancer diagnosis, treatment and prognosis. The first part of this review focuses on recently identified biomarkers for endometrial cancer, their importance in clinical use as well as the proteomic methods used in their discovery. The second part highlights some of the emerging mass spectrometry based proteomic technologies that promise to contribute to a better understanding of endometrial cancer by comparing the abundance of hundreds or thousands of proteins simultaneously.